Modern Techniques of Radiation Therapy in the Treatment of Brain Tumors and Tumors of the Skull Base - Diehl, Christian; Combs, Stephanie E. (Neurology International Open, 2018)
Today the choice of radiation oncology technique and treatment concept is highly individualized. Modern techniques enable the use of high local doses with significant sparing of normal tissue. This has significantly improved the therapeutic window. Molecular markers guide therapy decisions within the interdisciplinary context, for primary as well as secondary brain tumors. Skull base tumors benefit from highly precise radiation techniques; often, radiation therapy can be seen as a treatment alternative to surgery in this region.
Keywords: intensity-modulated radiation therapy; IMRT; stereotaxy; gliomas; brain metastases; skull base tumors